Impact of copper sulphate, potassium permanganate, and hydrogen peroxide on Pseudanabaena galeata cell integrity, release and degradation of 2-methylisoborneol. (15th June 2019) - Xu, Hangzhou; Brookes, Justin; Hobson, Peter; Pei, Haiyan
Abstract: Frequent off-flavor events caused by geosmin and 2-methylisoborneol have caused concern among consumers about the quality of potable water. Pseudanabaena galeata, a filamentous cyanobacterium, is a known producer of 2-methylisoborneol in lakes and reservoirs. The use of algicides to control cyanobacteria must consider the potential release of contaminants into the water. This is the first study to systematically investigate the effectiveness of copper sulphate (CuSO4 ), potassium permanganate (KMnO4 ), and hydrogen peroxide (H2 O2 ) on the cell viability and integrity of Pseudanabaena galeata. Following algicide or oxidant treatment, the release and degradation of 2-methylisoborneol was also examined. It is evident that all of these chemicals can decrease Pseudanabaena galeata viability and damage cell membranes and the filamentous Pseudanabaena galeata was more susceptible to treatment by these three algicides than unicellular colonial Microcystis aeruginosa . Of the three compounds used, KMnO4 showed the stronger ability to compromise cell integrity and 5.0 mg/L KMnO4 could induce 91 ± 1.5% lysis of Pseudanabaena galeata within 2 h. It was found that H2 O2 had the potential to degrade 2-methylisoborneol with 16.0 ± 0.4% degraded by 20.0 mg/L H2 O2 within 8 h. In contrast, 2-methylisoborneol could not be degraded by CuSO4 (dosage: ≤ 1.5 mg/L; reaction time: ≤ 8 h) and KMnO4 (dosage: ≤ 5.0 mg/L; reaction time: ≤ 3 h) basically. Results showed that the oxidation capacity of H2 O2 against Pseudanabaena galeata was enhanced under sunlight. The results will help drinking water utilities to better understand the risk of Pseudanabaena galeata lysis and 2-methylisoborneol release during raw water treatment. Graphical abstract: Image 1 Highlights: KMnO4 can lyse Pseudanabaena galeata faster than CuSO4 or H2 O2 under visible light. Pseudanabaena galeata was more susceptible to treatment than Microcystis aeruginosa . Among CuSO4, H2 O2 and KMnO4, only H2 O2 can partially degrade 2-MIB. The Delayed Chick Watson Model well describes the kinetics of cell rupture.